Preventing Violent Extremism in US: Updating the Strategy - Cameron, Sumpter (2016)
The United States executive branch has released an updated version of its 2011 strategy to prevent violent extremism through community engagement. While additions offer promise, effective implementation will need to overcome persistent problems of stigmatisation and mistrust.